A cognitive task approach on the influence of office automation software in secretarial practice - Musa, Muhammad Yahaya (2016)
Inefficiency in secretarial services in the application of office automation software has been of great concern to both secretaries and their employers. This inefficiency causes unnecessary delays in information processing and dissemination in the organization. The problem is rooted from the secretaries’ lacking in appropriate application of cognitive skills, proficiency in information handling as well as working experiences, and these establish the problem statement of the study. One of the important gaps this study has bridged is establishing the key elements that can assist the secretaries to perform their office tasks effectively. Efforts made to identify similar studies on secretaries’ profession were to no avail perhaps due to its non-availability or absence. It was discovered that the secretary’s level of applying perception and attention during working hours is extremely limited which contributed to poor or slow pace of service delivery. The objectives of this study are to explore the secretaries office automation software cognitive task, to investigate elements of office automation software cognitive tasks that influence secretarial practice and to investigate how office automation software supports the secretaries in the execution of tasks. Snowballing sampling was used to identify participants who have fulfilled a criterion set out in the study. Therefore, twelve (12) UTHM secretarial staff who are using office automation software in their office duties were chosen to participate in the study. The study employs qualitative method, thus interviews were carried out to collect data. Thematic data analysis was done using card index. Findings revealed that the secretaries need short and long term training in order to be relevant in their working places as well as to be updated in the use of office automation software. Further results revealed that office automation software supports the secretaries in the execution of cognitive tasks. The result also revealed the development of components of office automation software cognitive tasks in secretarial practice. These components were used by the secretaries in the execution of tasks such as word processing, scheduling of appointments and other secretarial duties. Another important finding revealed that, technology has changed the working environment of the secretaries which has made it imperative for them to continue using office automation software in the execution of their tasks. This has brought the idea of how office automation software supports the secretaries in the execution of their office tasks.